Early secreted antigenic target of 6-kDa protein of Mycobacterium tuberculosis primes dendritic cells to stimulate Th17 and inhibit Th1 immune responses - Wang, Xisheng (2012)
Early secreted antigenic target of 6 kDa (ESAT-6) of Mycobacterium tuberculosis is a T cell Ag that is a potential vaccine candidate, but it is also a virulence factor that mediates pathogenicity. To better understand the effects of ESAT-6 on the immune response, we studied the effect of ESAT-6 on human dendritic cells (DCs). Peripheral blood monocytes were treated with GM-CSF and IL-4 to yield immature DCs, which were matured by addition of LPS and CD40 ligand (CD40L), with or without ESAT-6. ESAT-6 inhibited LPS/CD40L-induced DC expression of costimulatory molecules, reduced DC-stimulated allogeneic T cell proliferation and IL-2 and IFN-γ production, and enhanced IL-17 production. ESAT-6-treated DCs also increased IL-17 and reduced IFN-γ production by M. tuberculosis-specific autologous T cells. ESAT-6 inhibited LPS/CD40L-induced DC production of IL-12 and enhanced that of IL-23 and IL-1β, without affecting secretion of TNF-α, IL-6, or IL-8 through specific interaction with immature DCs. The effects of ESAT-6 were not mediated through cAMP or p38 MAPK. Medium from ESAT-6-conditioned DCs increased IL-17 and reduced IFN-γ production by T cells stimulated with anti-CD3 plus anti-CD28, and ESAT-6-induced IL-17 production was blocked by neutralizing both IL-23 and IL-1β. ESAT-6 reduced LPS/CD40L-stimulated transcription of IL-12p35 and enhanced that of IL-23p19 through inhibition of IFN regulatory factor-1 and upregulation of activating transcription factor-2 and c-Jun, transcriptional regulators of IL-12p35 and IL-23p19, respectively. We conclude that ESAT-6 increases DC production of IL-23 and IL-1β while inhibiting that of IL-12, thus enhancing Th17 at the expense of protective Th1 responses.